Longitudinal study on the growth of motivation to lead : impact of quality of training experience and opportunity for leadership training. - Luo, Jingxian. (2010)
This study utilized a multi-wave longitudinal design to explore the growth pattern of an individual difference construct called the “Motivation to Lead” (MTL). Using multi-level modeling analysis, results from the multidimensional MTL construct (affective MTL, noncalculative MTL, and social-normative MTL) revealed differential growth trajectories for each of the MTL factor, demonstrating the dynamic nature of the construct. The study also investigated the effects of situational factors on MTL growth. Quality of training experience and opportunity for leadership training were found to have significant effect on the growth of MTL. The interaction effect of opportunity to leadership training and quality of training experience on MTL growth was only partially supported. Implications and suggestions for future research were discussed.